The Applicability of Contemporary, Classical Motivational Theories and Managerial Methods in Non-Western Countries - Dickson Scotch Mdhlalose (International Journal of Management, Accounting and Economics, 2024)
This study aims to comprehend the suitability of both traditional and modern motivational theories and managerial methods in non-Western nation's former colonies of the West like African countries. This study employed an exploratory research strategy to deepen our comprehension of the subject. This study only used third-party sources for its data. The application of motivational theories and managerial techniques may be limited by cultural contexts. Social norms have shaped the formation and maintenance of organizations within society that have a particular structure and way of functioning. Western motivational theories do not work in non-Western nations because indigenous people are rooted in their own culture and find it difficult to accept and let go of a foreign culture. This study contributes to the body of knowledge by analysing the applicability of motivational theories and managerial methods in non-Western countries. According to this study, local and international organizations specifically Western multinational organizations manage and motivate their workforce in non-Western nations by fusing management techniques with Western notions of motivation.
Keywords: 330; Employees; Managerial Methods; Motivational theories; Non-Western Countries; Organisation